Chromatographic separation of the free radical scavenging components of the leaf extracts of Leea philippinensis Merr. - Santiago, L. (2017)
The ability of Leea philippinensis, an endemic tree in the Philippines, as in vitro free radical scavenger was investigated. Soxhlet extraction using solvents in increasing order of polarity (hexane<chloroform<ethyl acetate<acetone<methanol) yielded acetone and methanol extracts with the highest Total Phenolic Content (TPC) and Total Flavonoid Content (TFC). These crude extracts were further separated using silica gel column chromatography with eluents hexane, hexane:acetone (1:1), acetone, acetone:methanol (1:1) and methanol. Fractions with the most TFC and TPC exhibited concentration-dependent activity with an IC50 value range of 0.10 - 0.29, 0.17 - 0.80, 0.29 - 0.84 and 3.40 - 9.75 mg/mL, respectively, against DPPH, hydroxyl, nitric oxide and hydrogen peroxide inhibition assays. In addition, these fractions demonstrated reducing power by transforming the Fe3+ to Fe2+. Infrared spectra of fractions at 4000–500 cm-1 using FTIR revealed presence of phenolic group.